2006
DOI: 10.1029/2005jd006497
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the altitude of fast upper tropospheric winds over the Northern Hemisphere during winter

Abstract: [1] The surface of maximum wind (SMW) is used as a frame for examining spatial and temporal variability in the vertical position of fast upper tropospheric winds over the Northern Hemisphere during winter. At a given observation time in a gridded data set, the SMW is defined as the surface passing through the fastest analyzed wind above each grid node, with a vertical search domain restricted to the upper troposphere and any tropospheric jet streams extending into the lower stratosphere. Documenting how SMW pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 79 publications
1
16
0
Order By: Relevance
“…To circumvent these potential difficulties, we use the Surface of Maximum Wind (SMW) analysis frame as described in Strong and Davis (2005, 2006a, 2006b, 2007. At a given observation time the SMW is the quasihorizontal surface that passes through the fastest wind in each column of the atmosphere with a vertical search domain restricted to the upper troposphere and any tropospheric jet streams extending into the lower stratosphere.…”
Section: The Surface Of Maximum Windmentioning
confidence: 99%
See 1 more Smart Citation
“…To circumvent these potential difficulties, we use the Surface of Maximum Wind (SMW) analysis frame as described in Strong and Davis (2005, 2006a, 2006b, 2007. At a given observation time the SMW is the quasihorizontal surface that passes through the fastest wind in each column of the atmosphere with a vertical search domain restricted to the upper troposphere and any tropospheric jet streams extending into the lower stratosphere.…”
Section: The Surface Of Maximum Windmentioning
confidence: 99%
“…Although mean properties of winter jet streams have been analysed in the context of temperature over the Northern Hemisphere (Koch et al, 2006;Strong and Davis, 2006a), jet core trends have yet to be assessed. Here, we measure the probability and speed of upper tropospheric jet stream cores over the Northern Hemisphere for winters 1958 to 2007, test for jet core trends, and identify the related tropospheric thermal structure changes.…”
Section: Introductionmentioning
confidence: 99%
“…The authors presented maps showing regional and seasonal trend variations and concluded that, in general, jet streams have moved poleward and risen to lower pressures in both hemispheres and weakened in the Northern Hemisphere. Previous studies of the boreal winter record also detected poleward jet stream contraction but found that jet stream core speeds increased extensively over the midlatitudes [ Strong and Davis , 2007], and showed that the leading pattern of jet stream pressure variability was an annular seesaw pattern linked to the Arctic Oscillation [ Strong and Davis , 2006, 2008]. Furthermore, Strong and Davis [2007] reported that positive jet stream wind speed trends are robustly indicated by geopotential height trends in three data sets: the ECWMF record since 1958, the NCEP record since 1958, and the satellite‐only portion of the NCEP record (1979–2007).…”
mentioning
confidence: 99%
“…Differences from Strong and Davis [2006, 2007, 2008] were not mentioned by Archer and Caldeira [2008], and stem largely from fundamentally different definitions for jet stream properties. Archer and Caldeira [2008] used columns of monthly mean data between 400 and 100 hPa to define jet stream properties as “mass and mass‐flux weighted averages of wind speed, pressure, and latitude” (see their equations (1)–(3)).…”
mentioning
confidence: 99%
See 1 more Smart Citation